Building Corporate Value Through Green Finance and Environmental Performance - Lubis, Tona Aurora; Yuliusman; Andang Fazri; Muhammad Haris Saputra (Cita konsultindo, 2025)
This study aims to analyze the Impact of Green Finance and Environmental Performance on Firm Value through Financial Performance. This objective is described as: 1) Analyzing the influence of Green finance, environmental performance and financial performance on firm value in Consumer Non-Cyclicals Sector Companies for the 2020-2023 Period 2) Analyzing the influence of Green finance and environmental performance on financial performance in Consumer Non-Cyclicals Sector Companies for the 2020-2023 Period 3) Analyzing the influence of Green finance and environmental performance on firm value through financial performance as a mediating variable in Consumer Non-Cyclicals Sector Companies for the 2020-2023 Period. This study is a quantitative study using SEM PLS. The results show that environmental performance has a positive and significant effect on financial performance, and financial performance is proven to have a strong and significant effect on firm value, while environmental performance does not directly affect firm value without the mediation of financial performance; On the other hand, Green Finance does not have a significant influence on either financial performance or company value, and is not proven to mediate the relationship, so it can be concluded that financial performance is a key factor that mediates the influence of environmental performance on company value, while green finance has not shown a significant contribution in the context of Consumer Non-Cyclicals sector companies in Indonesia for the period 2020–2023.